Pengaruh Pupuk Kandang Sapi, Npk Mutiara Terhadap Tanaman kacang Panjang (Vigna Sinensis L.) - Engelbertus Angkur; Ida Bagus Komang Mahardika; I Ketut Agung Sudewa (GEMA AGRO, 2021)
The study entitled "The Effect of Cow Manure Dose, Pearl NPK Against Long Beans (Vigan sinensis L.)". Aiming at knowing the growth, yield of long beans due to the dose of cow dung and NPK Mutiara. Conducted in February-April 2020. Using a Randomized Block Design (RBD) consisting of 2 factors: Cow Manure Dose, there are 3 levels: S0 (0 tons / ha), S1 (15 tons / ha) and S2 (30 tons) / ha ), NPK Mutiara fertilizer, there are 3 levels: M0 (0 kg / ha), M1 (150 kg / ha) and M2 (300 kg / ha). obtained 9 combinations, repeated 3 times. The results showed that there was no interaction between doses of cow dung and NPK Mutiara on the growth and yield of long beans, except for the fresh weight of brangkasang (P <0.05). Cow manure had a very significant effect (P <0.01) on the number of leaves, plant height, number of pods, pod weight, had no significant effect (P> 0.05) on pod length, fresh weight of stover, and oven dry weight of stover. NPK Mutiara fertilizer had a significant effect (P <0.05) on the number of leaves and pods, had no significant effect (P> 0.05) on other variables. The treatment dose of cow dung of 30 tonnes / ha (S2) gave the highest yield of 260.76 g on pod weight per plant, an increase of 32.35% compared to the lowest yield of 197.02 g at the treatment dose of 0 ton / ha of cow manure. (S0).